(untitled) (Journal of the Management Sciences, 2023)
This paper explores motivation as an office management tool for high productivity in commercial banks with focus on Aguata local government area of Anambra state. The research objectives included among others, the motivational strategies adopted by bank managers; and to find out if the strategies influence workers’ performances to enhanced productivity. The method adopted for this study was survey design. Taro Yamane’s simple random sampling technique was used to draw 50 bank workers as the sample to represent the population of 250 workers. Self-structured questionnaire was used as the major instrument of data collection. Tables and simple percentages were used for presentation of data and analysis. The study found out that motivational factors adopted by different bank management vary; that motivators for individual workers are not the same; that due to individual differences not all available strategies motivate every worker; that the planning and implementation of motivational schemes are too challenging to the bank management etc. The study concluded that motivation is an effective office management tool for enhanced productivity when the right application is made and at an appropriate time. Based on the findings, the following recommendations were proffered: that the bank management should do in-depth study of the real motivators for their workers based on individual differences; attention should be given to physical condition of the environment under which workers do their jobs etc.